Gestational diabetes mellitus and macrosomia: An analysis of secondary data - Mufdlilah Mufdlilah; Fijri Rachmawati (Journal of Health Technology Assessment in Midwifery, 2018)
Excessive fetal weight is considered as a health issues because it increases perinatal and maternal morbidity and mortality. The prevalence of macrosomia worldwide has increased over the past 2 to 3 decades. This study aimed to determine correlation between the incidence of gestational diabetes mellitus and macrosomia among pregnant women. The design of this study was analytical with a case control approach. Data used to analyze the incidence of macrosomia based on secondary data from 2014-2018. This research suggested that diabetes mellitus in pregnancy has a significant relationship with the incidence of macrosomia.